Comparison of physics syllabi on the diffraction concept in Indonesian, Malaysian, and International schools - Shahrul Kadri bin Ayop (Tanjung Malim, 2024)
Comparison of physics syllabi on the diffraction concept in Indonesian, Malaysian, and International schools by Shahrul Kadri bin Ayop